2013
DOI: 10.4103/0259-1162.114003
|View full text |Cite
|
Sign up to set email alerts
|

Addition of intrathecal fentanyl to bupivacaine clonidine mixture effect on quality of subarachnoid block and postoperative analgesia

Abstract: Context:This study was undertaken in 100 patients scheduled for lower limb orthopaedic surgeries.Aim:The objective of this study was to study the effect of addition of intrathecal fentanyl to bupivacaine clonidine mixture on the quality of subarachnoid block and compare it with intrathecal bupivacaine clonidine mixture without fentanyl.Settings and Design:In this prospective and double blind randomized controlled study, one hundred patients, between 20-40 years of age, of either sex, weighing between 40-65 Kg,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Our results are similar to those of Singh et al who observed no significant difference in HR and blood pressure in patients receiving 30 μg and 50 mcg of clonidine intrathecally undergoing cesarean section 13 . Similarly, Nazareth et al, also reported stable hemodynamic parameters in the groups receiving intrathecal clonidine and fentanyl combination 14 . However, Dobrydnjov et al reported significant decreases in patients receiving clonidine and fentanyl intrathecally.…”
Section: Discussionmentioning
confidence: 73%
“…Our results are similar to those of Singh et al who observed no significant difference in HR and blood pressure in patients receiving 30 μg and 50 mcg of clonidine intrathecally undergoing cesarean section 13 . Similarly, Nazareth et al, also reported stable hemodynamic parameters in the groups receiving intrathecal clonidine and fentanyl combination 14 . However, Dobrydnjov et al reported significant decreases in patients receiving clonidine and fentanyl intrathecally.…”
Section: Discussionmentioning
confidence: 73%
“…[ 12 ] and Nazareth et al . [ 14 ] also reported mild to moderate degree of sedation in the clonidine groups. Clonidine is known to cause sedation, and this hypnotic response is believed to be mediated via locus coeruleus where alpha-2-adrenergic receptors are abundant.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were reported by Nazareth et al . [ 14 ] who obtained corresponding duration of motor block in the intrathecal clonidine group and in a group where combination of intrathecal clonidine and fentanyl were administered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation